University Leadership: Transparency in Communication with External Stakeholders - Nadiia Artyukhova; Olena Churikanova; Kseniia Bliumska-Danko (Business Ethics and Leadership, 2024)
The research offers valuable insights into the importance of transparency in building trust, accountability, and a positive reputation for universities in Ukraine. The relevance of this topic is underscored by the growing global emphasis on the need for higher education institutions to communicate transparently with external audiences, including prospective students, parents, funding agencies, and the general public. Transparency in financial operations, governance, and academic offerings has become crucial for universities to attract talented individuals, secure financial support, and develop lasting partnerships. The study's methodology – the K-means clustering technique ‒ effectively assesses university transparency. It clusters institutions based on shared transparency characteristics, allowing for the identification of distinct patterns and the classification of Ukrainian universities into specific groups. This approach provided a comprehensive understanding of universities' performance in external communication. The Elbow Method was employed to establish the ideal number of clusters, dividing universities into four main clusters, each demonstrating varying degrees of transparency. The findings revealed that universities across different clusters exhibited unique transparency profiles. While some universities performed exceptionally well across multiple transparency criteria, others showed significant shortcomings, particularly in budget reporting and staff transparency. The results indicated that some universities emerged as transparency leaders, serving as models for others, while those in lower-performing clusters require targeted improvements in their communication strategies. The study highlights the practical impact of transparency on university governance and engagement with stakeholders. Universities that prioritize transparency build trust with external audiences and strengthen internal decision-making processes. The clustering method provided essential insights into which institutions lead in transparency and where improvements are necessary, reinforcing that transparency is key to ensuring competitiveness within the higher education landscape. This research broadens the understanding of transparency in higher education, offering practical recommendations for universities seeking to enhance their external communication practices. The study underscores the importance of aligning these efforts with international transparency standards to ensure long-term success and maintain credibility in the increasingly competitive global academic environment.